PENGARUH PROMOSI DAN HARGA MENUTERHADAP PENDAPATAN PADA OKOH JAPANESE RESTAURANTDI HOTEL HORISON BANDUNG - Adrian Novandra, - (2009)
This observation's purpose is to find out the influences of promotion cost and price menu to income at Okoh Japanese restaurant on horison hotel Bandung. As independent variable indicator (X1) observer use 20 three-month periodic promotion cost report and (X2) is price menu, the average of price menu increase for 20 three-month periodic. Dependent variable indicator is income (Y) for 20 three-month periodic. This observation is a descriptive analysis method. The result shows that all free variables which coverage promotion cost variable (X1) and price menu variable (X2) has a real influence to Okoh Japanese restaurant for 81,82%, and for the rest, 18,18% is influenced by another variable outside the two variable that being analyze. The result shows that promotion cost variable (X1) to Income has a positive influence for 0,8175 or 81,75%, means that the increase of promotion cost variable will also increase the Income, while price menu variable (X2) has 0,0007 or 0,007% positive influence to Income.